Pengembangan Elektronik Modul (E-Modul) Interaktif Berbasis Web Dengan Pendekatan Saintifik Pada Materi Ikatan Kimia - Anisa Lailatul Azizah; Ardhana, Ivan Ashif (LPPM Universitas Negeri Jakarta, 2023)
This purpose of this study is to (1) produce web-based interactive E-modules with a scientific approach to chemical bonding materials;(2) knowing the feasibility and effectiveness of web-based interactive E-modules with a scientific approach to chemical bonding materials. The subjects were 24 students of class X MIPA 2 at MAN 1 Trenggalek.. The method used in this study is a development research with a 4D development model from Thiagarajan which stages are define, design, develop, and disseminate. However, this study was limited to the third stage due to time and energy constraints. Validation is carried out by 1 chemistry lecturer and 1 chemistry teacher. The results of this study (1) E-module developed with 3 stages including define, design, and develop using canva software. This E-module uses the 5M of scientific approach syntax. (2) Eligibility of the E-Modules obtains of percentage of 80% in the appropriate category from material experts and 95.65% in the very feasible category from media experts. While the effectiveness of E-Modules obtained a percentage of 83.3% with a very effective category. Based on the results of expert validation tests and effectiveness tests, this E-module is declared feasible and effective to be used as a learning medium for students.